Isolasi dan Identifikasi Fungi Endofit Tanaman Suruhan (Peperomia pellucida L. Kunth) - Rosa, Lidiya Praktika; Wahyuni, Dwi; Murdiyah, Siti (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Plants Suruhan (Paperomia pellucida L. Kunth) has traditionally been used as a drug abscesses, boils acne, skin diseases, headaches, relieve pain in arthritic.Various properties owned by the plant Suruhan make this plant as a major commodity medicinal plants are cultivated by the people. Suruhan pharmacological function can not be separated because their secondary metabolites that allegedly resulted from their symbiosis with endophytic microbes such as fungi. Endophytic fungi are microscopic fungi that live intracellularly in the plant tissue without damaging the host. This study aimed to isolate and identify endophytic fungi on plant fruit organs errand. Isolation of endophytic fungi on errands obtained 15 isolates comprising of Fusarium sambucinum, Cladosporium cladosporoides, Cladophialophora sp. Myrothecium sp., Gliocladium sp., Penicillium expansum, Aspergillus sp., Aspergilus niger, Lichtheimia sphaerocystis dan Absidia corymbifera.